Characteristics of enzymolysis of silkworm pupa protein after tri-frequency ultrasonic pretreatment: kinetics, thermodynamics, structure and antioxidant changes - Ge, Shuangmei; He, Chunyan; Duan, Yichen; Zhou, Xiaotao; Lei, Jialong; Tong, Xiangyun; Wang, Libing; Wu, Qiongying; Jia, Junqiang (Frontiers in Bioengineering and Biotechnology, 2023)
As a by-product of the sericulture industry, the utilization rate of silkworm pupa resources is currently not high. Proteins are converted into bioactive peptides through enzymatic hydrolysis. Not only can it solve the utilization problem, but it also creates more valuable nutritional additives. Silkworm pupa protein (SPP) was pretreated with tri-frequency ultrasonic (22/28/40 kHz). Effects of ultrasonic pretreatment on enzymolysis kinetics, enzymolysis thermodynamics, hydrolysate structure as well as hydrolysate antioxidant of SPP were investigated. Ultrasonic pretreatment significantly increased the hydrolysis efficiency, showing a 6.369% decrease in km and a 16.746% increase in kA after ultrasonic action (p < 0.05). The SPP enzymolysis reaction followed a second-order rate kinetics model. Evaluation of enzymolysis thermodynamics revealed that Ultrasonic pretreatment markedly enhanced the SPP enzymolysis, leading to a 21.943% decrease in Ea. Besides, Ultrasonic pretreatment significantly increased SPP hydrolysate's surface hydrophobicity, thermal stability, crystallinity, and antioxidant activities (DPPH radical scavenging activity, Fe2+ chelation ability, and reducing power). This study indicated that tri-frequency ultrasonic pretreatment could be an efficient approach to enhancing the enzymolysis and improving the functional properties of SPP. Therefore, tri-frequency ultrasound technology can be applied industrially to enhance enzyme reaction processes.